Land rights for African development: from knowledge to action - Mwangi, Esther (CGIAR, 2006)
A wide range of issues are captured and reiterated in the 12 briefs contained in this collection. These include: the prevalence and importance of customary tenure; the prevalence and importance of common property arrangements; constraints to women’s access under both customary and statutory tenure; the need to secure common property and other forms of tenure; and the importance of broad based participation to secure broad consensus among multiple actors in order to enhance the efficiency, equity and sustainability objectives of land tenure reforms. The briefs also reflect on the innovations necessary for securing tenure for the poor under a variety of settings. These innovations include: • adjusting received law to customary norms and rules of land holding and access, as opposed to outright replacing customary tenure • altering lending rules by banks and financial institutions to promote land-related investments (even on land regulated by customary and/or religious law) • de-emphasizing the notion of ownership and refocusing on use rights in order to secure women’s rights and access • restructuring conventional land administration systems to support group-based rights structures • encouraging decentralized land management systems that reflect local cultural norms and practices • in situations of multiple, overlapping resource use, strengthening processes of negotiation and conflict resolution as opposed to a generic concern with substantive rights in order to secure the access of permanent and transitory resource users.